Comparison of emotional processing assessed with fear conditioning by interpersonal conflicts in patients with depression and schizophrenia. Issue 3 (25th December 2018) - Tani, Hideaki; Tada, Mitsuhiro; Maeda, Takaki; Konishi, Mika; Umeda, Satoshi; Terasawa, Yuri; Mimura, Masaru; Takahashi, Takuya; Uchida, Hiroyuki
Abstract : Aim: While emotional processing is implicated in various psychiatric illnesses, its differences among diagnoses are unclear. We compared associative learning of social values in patients with depression and schizophrenia by measuring skin conductance response to interpersonal stimuli. Methods: We included 20 female outpatients each with depression and schizophrenia. They underwent Pavlovian conditioning experiments in response to a classical aversive sound, and an interpersonal stimulus that was designed to cause aversive social conditioning with actors' faces coupled with negative verbal messages. Multiple regression analysis was performed to examine the associations between the degree of conditioned response and the clinical characteristics of the participants. Results: Conditioned responses during the acquisition phase in both conditions were higher in depression compared to schizophrenia. Patients with depression successfully showed fear conditioning in both conditions, and they exhibited slower extinction in the interpersonal condition. The conditioned response during the extinction phase showed a positive association with Emotion Regulation Questionnaire Expressive Suppression score, and a negative association with the Emotion Regulation Questionnaire Cognitive Reappraisal score and the use of antidepressants. Patients with schizophrenia did not become conditioned in either of the conditions. The Positive and Negative Syndrome Scale Negative Syndrome score was negatively associated with the degree of conditioned response during the acquisition phase in the interpersonal condition. Conclusion: Female patients with schizophrenia, especially those who prominently demonstrated negative symptoms, suggested their intrinsic impairments in the associative learning of social context. Antidepressants and adaptive emotional regulation strategy may enhance the extinction learning of aversive social conditioning in depression.